Potential Functional Implications of Pearl millet (Pennisetum glaucum) in Health and Disease - Vanisha S. Nambiar, JJ Dhaduk, Neha Sareen, Tosha Shahu, Rujuta Desai (Journal of Applied Pharmaceutical Science)
Pearl millet (Pennisetum glaucum), also known as Bajra, is one of the four most important cereals (rice, maize, sorghum and millets) grown in tropical semi-arid regions of the world primarily in Africa and Asia. Our aim is to review the potential health benefits of pearl millet. Desk reviews from Gujarat Agricultural Universities, libraries, PubMed and other web sources, key informant interviews of farmers (n=30), local leaders (sarpanch) (n=30) and women (n=960) from pearl millet belt of Banaskantha district of Gujarat. Pearl millet is rich in several nutrients as well as non-nutrients such as phenols. It has high energy, has less starch, high fiber (1.2g/100g, most of which is insoluble), 8-15 times greater α-amylase activity as compared to wheat, has low glycemic index (55) and is gluten free. The protein content ranges from 8 to 19% and it is low in lysine, tryptophan, threonine and the sulfur-containing amino acids. The energy of millet is greater than sorghum and nearly equal to that of brown rice because the lipid content is generally higher (3 to 6%). Pearl millet can be recommended in the treatment of celiacdiseases, constipation and several non-communicable diseases. Nutritional studies on the population living in the pearl millet belts of the world and clinical trials on the impact of pearl millet in specific disease conditions are needed.
Keywords: Pearl millet, review, health, Banaskantha, NCDs